(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
Ageing is a physiological phenomenon that manifested itself with disturbances of many homeostatic regulating mechanisms of the body . The present study was conducted and employed to investigate two major systems( hormones and antioxidant systems) that can be implicated in progress of aging .The total number of subjects included in the present study was fifty (50) healthy men and classified according to their ages into two groups, the first group included 25 younger men (control group) and their ages ranged between 21 to 30 years old whereas the second group included 25 older men and their ages were between 61 to 70 years old. Data obtained from this study indicated a significant decrease(p<0.05) in the levels of thyroid stimulating hormone (TSH) which is associated with marked elevation (p<0.05) of triiodothyronine(T3) and tetraiodothyronine(T4) of older men when compared with younger men. In regard to levels of cortisol and testosterone hormones were significantly decreased (p<0.05) in aged men when matched with their counterparts of younger men. Concerning concentrations of malondehyde (MDA) ,a final product of lipid peroxidation, confirmed a remarkable elevation (p<0.05) in older men compared to younger men and these results were associated with significant lowering (p<0.05) in the activities of antioxidant components including glutathione peroxidase (GPX), reduced glutathione (GSH) and catalase . In addition , there are no significant correlations(p>0.05) occurring among hormones( testosterone , T3) and glutathione peroxidase and of malondehyde . From these results ,one can be concluded that with ageing there are many disturbances and fluctuations of hypothalamic-adrenal and thyroid axis that accompanied with drop of essential antioxidant components that may be lead to suppress of defense against free radicals and the present study concluded that the changes occurring in studied hormones have not relations and effects on the antioxidant systems.